Controlling factor for nature, pattern and accumulation of the glacial sediments of Schirmacher Oasis, East Antarctica: Comments on paleoclimatic condition - Srivastava, A.K.; Ingle, P.S.; Khare, N. (Polar Science, 2018)
The Schirmacher Oasis, East Antarctica is clearly distinguishable into three geomorphologic units i.e., i) polar ice sheet, ii) main rocky land including lakes, and iii) coastal shelf. These units have different processes for the release and accumulation of sediments because of various physical and chemical factors operating either individually or, in combination. The cumulative effect of these factors is the accumulation of sediments which are normally represented by loose admixture of clasts, sand, silt and clay. Sedimentological studies of these sediments provide a good idea about various endogenic and exogenic processes going on in the area and their affect on nature and pattern of sedimentation as well as paleoclimatic conditions, hydrodynamic, depositional setup, clay mineralization. In the present work, compilation and reinterpretation of the work carried out in the past on the aspects of granulometry, heavy minerals and clay minerals have been carried out together for various geomorphological units and entire area together to interpret various factors responsible for sediment accumulation. It has been observed that wind, melt water and ice are the main controlling factors for the present scenario of nature and composition of glacial sediments of the Oasis. Comments have also been made on the paleoclimatic conditions. journal article